The mask paradox between perception of discomfort and reality of physiological effects in healthy college students in China: a panel study - Songtao Wang; Jiayuan Hao; Qianyi Ruan; Xuanxuan Hong; Zicheng Yu; Jiawen Huang; Jiayi Li; Dongna Gao; Suyang Liu (BMC Public Health, 2024)
Abstract Background During the COVID-19 pandemic, masks proved to be an effective measure in preventing virus transmission. However, many people have reported discomfort and negative perceptions toward wearing masks, especially during physical activity. This study aims to evaluate the discomfort and adverse perceptions related to various mask types among young, healthy adults during light exercise, including sitting, stationary stepping, and stair climbing. The study also examines the extent to which masks influence physiological indicators of physical well-being. Methods The study was conducted in two stages at the campus hospital of Shantou University. In Stage 1, 20 healthy college students (10 males, 10 females) were recruited to identify the mask with the most substantial physiological and psychological impact among four types: KN95 respirators, surgical masks, cloth masks, and 3D medical masks. These specific types were chosen due to their widespread use and varying levels of filtration and breathability. In Stage 2, 14 healthy college students (7 males, 7 females) were included to examine the effects of the identified mask across various levels of physical exertion. Subjective perceptions were measured using the Mask-Related Discomfort and Perception Score (MRDPS), and physiological parameters such as body temperature, blood pressure, pulse rate, and vital capacity were recorded. Results The KN95 respirator and cloth mask were associated with the highest MRDPS, indicating significant discomfort among wearers (p < 0.05). The use of KN95 respirators had the largest impact on MRDPS during stair stepping (β = 10.357, 95% CI [5.755, 14.959]). Physiological parameters showed minor variations across different masks, with KN95 respirators significantly associated with reduced diastolic blood pressure (β=-7.806, 95% CI [-12.294, -3.318]) and pulse rate (β=-10.661, 95% CI [-18.896, -2.425]) in Stage 1. However, after controlling for exercise pace in Stage 2, wearing a KN95 respirator did not significantly affect these parameters. Conclusions KN95 respirators and cloth masks were found to cause the most discomfort during light physical activity, with males reporting higher discomfort levels than females. While these masks are associated with varying levels of perceived discomfort, their impact on physiological indicators is relatively modest. Future research should include larger and more diverse samples , continuous monitoring of physiological parameters during exercise, and exploration of the underlying mechanisms of gender differences in mask discomfort.